Design Recovery of Student Information Legacy System (International Journal of Engineering and Computer Science, 2014)
Reverse engineering for software is the process of analyzing a program in an effort to create a representation of the program at a higher level of abstraction than source code. Reverse engineering is a process of design recovery. Reverse engineering tools extract data, architectural, and procedural design information from an existing program. This paper explores the application of reverse engineering in recovering the design of a legacy student information system developed using Dbase V atUsmanuDanfodiyo University Sokoto using UML based approach. Use case model is used in recovering the design specifications (i.e., functionalities)of the student information system. In addition,object oriented design model for the system is proposed using class diagramso that the system can be implemented using object oriented programming.